G360 The epidemiology and outcome of biliary atresia in scotland 2002–2013. (27th April 2015) - Sutton, E; Henderson, P; Tayler, R; Fraser, K; Cowieson, J; Goudie, D; McIntyre, K; Kastner-Cole, D; Cameron, C; Loganathan, S; Rogers, P; Mitchell, D; et al.
Abstract : Background: Biliary atresia (BA) is a rare, poorly understood liver disease of infancy that is fatal if not treated through early biliary drainage via the Kasai procedure. BA surgery was rationalised to three UK centres in 2002 following data supporting improved outcomes in institutions performing >5 Kasai per year. We have previously shown that outcomes in Scottish children were worse than expected in the years following initial rationalisation. Aims: We aimed to expand the post-rationalisation cohort of BA cases in Scotland to examine epidemiology and outcomes. Methods: Outcomes of the previously published 2002–2009 incident cohort was first expanded. New Scottish incident cases of BA born between 2010–2013, were obtained using data from specialist nurse/team knowledge. New data collection focussed on demographics, details of Kasai and outcomes (particularly 2 year transplant-free survival [2YTFS]). Accurate regional and national population data was obtained from the General Register Office for Scotland and statistics performed in R with Poisson regression analysis for incidence trends. Results: 48 infants were initially identified, of whom 5 were excluded from outcome analysis (three with Kasai performed in Edinburgh, one with <1 yr follow-up post-Kasai and one born outside Scotland). Three infants required immediate liver transplantation; 43 infants underwent Kasai. Median age at Kasai in the full cohort was 55 days (range 19–96) and showed significant improvement from 61 days in 2002–2009 to 49 days in 2010–2013 (p < 0.0001). Of those with available data, 45% cleared their jaundice (bilirubin <20 umol/l) six months post-Kasai; 2YTFS was 40%. BA incidence in Scotland was 0.68/10, 000 live births and appeared stable (0.66/10, 000 in 2002–2009, 0.71/10, 000 in 2010–2013). A cluster of cases was identified in Lanarkshire where the incidence was 1.26/10, 000 live births, significantly higher than the rest of Scotland (0.59/10, 000, p = 0.033). Conclusion: BA atresia incidence appears relatively stable in Scotland but with an unexplained cluster of cases in Lanarkshire; examination of this cluster may provide epidemiological insight into disease pathogenesis Despite a significant reduction in time to Kasai, the 2YTFS in Scotland remains disappointing, is lower than the pre-rationalisation figure of 65% and is not currently an endorsement of centralisation of BA surgery in Scotland.